Kajian Kualitas Dan Tingkat Pelayanan Jalur Pejalan Kaki (Studi Kasus: Sepanjang Jalan Jend. Ahmad Yani Kota Bekasi) - Daffa Dwi Saputra; Djoko Suwandono (Teknik PWK (Perencanaan Wilayah Kota), 2022)
This study aims to determine the quality and service level of pedestrian paths. This research is based on the problems that exist in the pedestrian path along Jalan Jend. Ahmad Yani Kota Bekasi which is an urban center. The problems that occur at the location of this study are the damage to the pedestrian path and the occurrence of a change in the function of the pedestrian path which is mostly used by motorized vehicle parking which is an obstacle to the pedestrian path. This study uses the calculation of the Pedestrian Environmental Quality Index (PEQI) and the Pedestrian Level of Service (High Capacity Manual). The method used in this research is by using quantitative methods and the analysis carried out is descriptive analysis. Based on the results of the analysis carried out, the value of the quality of the pedestrian crossing is in the acceptable category (Class II) where the facilities and infrastructure for the intersection are sufficient for road users, while for the quality of the pedestrian lane itself it is in a bad category (Class IV) due to the condition of the path that is perforated as well as the obstacles or obstacles that occur on the pedestrian path itself. The results of the service level analysis are based on the flow and based on the entry space at the service level c (basic service level).